Extratos do resíduo de amora-preta (Rubus fruticosus) : microencapsulação por spray dryer - Santos, Suelen Siqueira dos (2017)
The blackberry (Rubus fruticosus) is a fruit belonging to the family Rosaceae, genus Rubus, with 400 to 500 species, known as berries. The berries are small fruits, with sweet taste and rounded format, characterized by their high antioxidant potential due to the contents of total phenolic compounds and flavonoids. In addition, they have high content of anthocyanins, mainly anthocyanin cyanidin 3-glucoside. In fruit processing industries, about 20% of pomace is produced, basically composed of seeds and barks that still contain a large amount of phenolic compounds, such as anthocyanins. The limiting factor for the use of anthocyanins is their lower stability, being affected by several parameters such as pH, copigmentation, light, temperature and oxygen. In orther to minimize these adverse effects, microencapsulation can assist with many useful properties, the encapsulation provides a degree of stabilization for active compounds, avoiding deteriorating reactions...